Heterodiscursividade E Memória Da Língua: Uma Análise Dialógica Da Repercussão Midiática Do Exemplo `Nós Pega O Peixe" No Livro Didático `Por Uma Vida Melhor" - Araujo, Elvis Lima De [UNIFESP] (2018)
This Thesis Purposes, As Its General Objective, To Verify The Update Of The Discourse About Teaching Portuguese Language At The Communicative Chain Built About Nós Pega O Peixe (We Catches The Fish, In A Free Translation), From The Repercussion At Online Media Of An Hypothetical Example In A Chapter Of A Didactic Book Which Verses On Brazilian Vernacular. The Temporal Frame Evokes The Year Of 2011, When The Didactic Book Por Uma Vida Melhor (For A Better Life, In A Free Translation), Developed To The Teaching Modality Education Of Young And Adults (Eja, In Portuguese) Was Released To Brazilian Public School, Suggesting A Proposal Of Discussing Linguistic Diversities With The Purpose Of Developing A Scenery Which Provide Clues On The Diversity Of Brazilian Portuguese. Especially By The Point Of View Of Heterodirscursivity, The Problem Of The Disjunction Between The Discourse About The Portuguese That Was Supposed To Be Taught And The Language Practiced At Many Quotidian Communicative Situations And The Impact